Male nursing students’ experiences of their clinical internships: A qualitative study - Yitao Zhou; Lingyan Weng; Menglu Wang; Ganying Huang (Heliyon, 2024)
Background: Nursing has traditionally been a predominantly female profession; however, there has been a gradual increase in the proportion of male nursing students in recent years. Male nursing students may encounter distinct challenges within clinical settings, potentially impacting their physical and mental well-being. Aim: This study aims to explore the clinical internship experiences of male nursing students and provide them with adequate support for their successful adaptation to clinical roles. Methods: This study used a descriptive design and qualitative approach. The participants were enrolled using a convenience sampling method. Data were collected using individual face-to-face semi-structured interviews. Results: Male nursing students’ experiences of their clinical internships were described through the following themes: (1) dynamics of working as a nurse, (2) not just a male nursing student, (3) gender-based stereotypes, (4) balance between forte and failing, (5) difficulties and challenges when working in hospitals, and (6) lessons learned and knowledge needs. Conclusions: Our research findings have significantly enhanced our comprehension of male nursing students' experiences and offered valuable recommendations for both nursing education and clinical practice. Simultaneously, these results provide essential information support for nursing educators and hospital administrators.